A gene expression signature associated with B cells predicts benefit from immune checkpoint blockade in lung adenocarcinoma. (1st January 2021) - Budczies, Jan; Kirchner, Martina; Kluck, Klaus; Kazdal, Daniel; Glade, Julia; Allgäuer, Michael; Kriegsmann, Mark; Heußel, Claus-Peter; Herth, Felix J.; Winter, Hauke; Meister, Michael; Muley, Thomas; et al.
ABSTRACT: Immune checkpoint blockade (ICB) expands the therapeutic options for metastatic lung cancer nowadays representing a standard frontline strategy as monotherapy or combination therapy, as well as an option in oncogene-addicted NSCLC after exhaustion of targeted therapies. Predictive markers are urgently needed, since only a minority of patients benefits from ICB, while serious adverse effects of immunotoxicity may occur. The study cohort included 43 ICB-treated metastatic lung adenocarcinoma showing long-term response (n = 16), rapid progression (n = 21) or intermediate patterns of response (n = 6). Lung biopsies acquired before initiation of ICB were analyzed by targeted mRNA expression profiling of 770 genes. Level and proportions of 14 immune cell types were estimated using characteristic gene expression signatures. Abundance of B cells (HR = 0.66, p = .00074), CD45+ cells (HR = 0.61, p = .01) and total TILs (HR = 0.62, p = .025) was associated with prolonged progression-free survival after ICB treatment. In a ROC analysis, B cells (AUC = 0.77, p = .0055) and CD45+ cells (AUC = 0.73, p = .019) predicted benefit of ICB, which was not the case for PD-L1 mRNA (AUC = 0.54, p = .72) and PD-L1 protein expression (AUC = 0.68, p = .082). Clustering of 79 candidate predictive markers identified among 770 investigated genes revealed two distinct predictive clusters which included cytotoxic cell or macrophage markers, respectively. In summary, targeted gene expression profiling was feasible using routine diagnostics biopsies. This study proposes B cells and total TILs as complementary predictors of ICB benefit in NSCLC. While further preferably prospective validation is required, gene expression profiling could be integrated in the routine diagnostic work-up complementing existing NGS protocols.